PENGARUH HEALTH EDUCATION TERHADAP PENINGKATAN MOTIVASI KEPALA KELUARGA DALAM MENCEGAH TERJADINYA DHF DI RT 1 KELURAHAN KOTA PAGATAN KUSAN HILIR TANAH BUMBU - Heri Triwibowo; Rahmad Hidayattullah (STIKes William Booth Surabaya, 2017)
Introductions: The high incidence of dengue fever occurs because of the behavior of society that harms the health and motivation of the people who lack in maintaining personal hygiene and environment, it will cause the risk of DHF transmission in the family and community. The purpose of research to determine the effect of health education to increase family head motivation in preventing the occurrence of Dengue Hemorrhagic Fever. Methods: The design of this research is pre experiment type one group pre test-post test design. Population of research that is all of Head of Family in RT 1 Kota Pagatan Village Kusan Hilir District Tanah Bumbu Regency as much as43 Head of Family. The sample was taken by random sampling technique as many as 39 Head of Family. There are two research variables that are counseling as independent variable and family head motivation in preventing DBD as dependent variable. Instrument used is questionnaire sheet and analyzed by Wilcoxon test. Results: The results showed that the value of ρ = 0.00, <α = 0.05 then H0 rejected means there is influence of health education to increase family head motivation in preventing the occurrence of Dengue Fever. Discussions: The results showed that counseling can affect the motivation of the head of the family in preventing dengue hemorrhagic fever. The family should keep trying to increase its knowledge about prevention of DHF so that it can increase family motivation in doing DHF prevention can be more increase.